2004
DOI: 10.1099/mic.0.26992-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of NblA, a protein involved in phycobilisome turnover, during heterocyst differentiation in cyanobacteria

Abstract: In unicellular non-diazotrophic cyanobacteria, NblA is a small polypeptide required for phycobilisome degradation during macronutrient limitation. In the filamentous N2-fixing Tolypothrix sp., a nblA gene (nblAI) lies upstream of the cpeBA operon that encodes phycoerythrin apoproteins. Using a specific anti-NblAI antibody it was found that in strains of Tolypothrix sp. NblAI abundance increases under nitrogen-limiting conditions but the protein is also present in cells grown in nitrogen-replete medium. Gold im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The designation, NblA, reflects the 'nonbleaching' phenotype of the knockout-mutant, which remains blue-green under conditions that trigger phycobilisome degradation, in contrast with the wild type that turns yellowish or bleaches. Orthologs of NblA of S. elongatus (proteins of~6-7 kDa) have been identified in a variety of cyanobacteria and red algae (Baier et al, 2001(Baier et al, , 2004Richaud et al, 2001;Li and Sherman, 2002;Luque et al, 2003;de Alda et al, 2004;Kawakami et al, 2009). Transcription of nblA, which is induced by specific environmental cues, is subject to complex and tight regulation (Schwarz and Grossman, 1998;Sauer et al, 1999;Luque et al, 2001;van Waasbergen et al, 2002;Osanai et al, 2005;Sendersky et al, 2005;Lahmi et al, 2006;Salinas et al, 2007;Zabulon et al, 2007;Kato et al, 2008Kato et al, , 2011Ruiz et al, 2008;Leganes et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The designation, NblA, reflects the 'nonbleaching' phenotype of the knockout-mutant, which remains blue-green under conditions that trigger phycobilisome degradation, in contrast with the wild type that turns yellowish or bleaches. Orthologs of NblA of S. elongatus (proteins of~6-7 kDa) have been identified in a variety of cyanobacteria and red algae (Baier et al, 2001(Baier et al, , 2004Richaud et al, 2001;Li and Sherman, 2002;Luque et al, 2003;de Alda et al, 2004;Kawakami et al, 2009). Transcription of nblA, which is induced by specific environmental cues, is subject to complex and tight regulation (Schwarz and Grossman, 1998;Sauer et al, 1999;Luque et al, 2001;van Waasbergen et al, 2002;Osanai et al, 2005;Sendersky et al, 2005;Lahmi et al, 2006;Salinas et al, 2007;Zabulon et al, 2007;Kato et al, 2008Kato et al, , 2011Ruiz et al, 2008;Leganes et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…6A) exists with the homologue in cyanophage Ma-LMM01, which belongs to the Myoviridae (64). In cyanobacteria, NblA has been demonstrated to be a key protein of thylakoid and phycobilisome degradation and to result in a color change of cyanophage cultures from normal blue-green to chlorotic yellow (2,7,9). To reveal the function of PaV-LD NblA, we expressed the NblA fusion protein and prepared the anti-NblA antibody.…”
Section: Feature Ofmentioning
confidence: 99%
“…It may be possible that the NblA protein of S. elongatus is rapidly degraded together with the PBS and, therefore, is not accumulated to a detectable level. Previous studies, however, indicated the presence of NblA from Tolypothrix PCC 7601 and Synechocystis PCC 6803 (16,42,43); thus, it may be suggested that NblA stability differs between various cyanobacterial strains (see "Discussion").…”
Section: The Cellular Level Of the Nbla Protein In S Elongatus Remaimentioning
confidence: 90%
“…Previous studies based on in vitro interaction of NblA with the PBS suggested that the protein interacts directly with rod components (16,42,43). The most detailed study was performed by Bienert et al (18) who identified interactions in vitro with PC and PEC and assigned critical roles for Leu-51 and Lys-53 (numbering according to the Anabaena chromosomal NblA sequence), located at the C terminus of the second helix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation